2011
DOI: 10.1111/j.1749-6632.2011.06390.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging and consumer decision making

Abstract: Research on consumer decision making and aging is especially important for fostering a better understanding of ways to maintain consumer satisfaction and high decision quality across the life span. We provide a review of extant research on the effects of normal aging on cognition and decision processes and how these age-related processes are influenced by task environment, meaningfulness of the task, and consumer expertise. We consider how research centered on these topics generates insights about changes in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 81 publications
(164 reference statements)
2
46
0
6
Order By: Relevance
“…Atrophy is clinically corroborated by an alteration of cognitive abilities, particularly executive functions. Various studies have demonstrated that verbal fluency, attention span, working memory and planning skills [21][22][23][24][25][26][27][28] also show an age-related decline. The performance of inhibition tasks is particularly affected [21,29].…”
Section: Alteration Of Processing Speedmentioning
confidence: 99%
See 3 more Smart Citations
“…Atrophy is clinically corroborated by an alteration of cognitive abilities, particularly executive functions. Various studies have demonstrated that verbal fluency, attention span, working memory and planning skills [21][22][23][24][25][26][27][28] also show an age-related decline. The performance of inhibition tasks is particularly affected [21,29].…”
Section: Alteration Of Processing Speedmentioning
confidence: 99%
“…Yet, when the speed of information processing is controlled in clinical research, the cognitive alterations previously described are significantly reduced [22,23,25,30,[33][34][35][36]. This is particularly true for tasks requiring mental flexibility, in which the decrease in processing speed is more prominent than difficulties in the analysis [25,33].…”
Section: Alteration Of Processing Speedmentioning
confidence: 99%
See 2 more Smart Citations
“…Other study, Hamilton (2009) revealed significant association of poverty narrative and household decision making. Yoon and Carpenter (2013) examined the effect of aging and consumer decision making, and a study by Hall et al (1995) claimed that high and low involvement products are associated with gender, family structure in relation to family decision making. Maguire and Zhang (2016); Richard and Masud (2016) identified that cultural intermediaries personal, consuming preferences and practices are significant to buying decision making.…”
Section: Theoretical and Empirical Aspect Of Consumer Decision Makingmentioning
confidence: 99%